The Context of Religious and Spiritual Care at the End of Life in Long-term Care Facilities* - Hamilton, V. Lee (Oxford University Press, 2009)

(untitled)
Despite the increasing numbers of Americans who die in nursing homes (NHs) and residential care/assisted living (RC/AL) facilities, and the importance of religious and spiritual needs as one approaches death, little is known about how these needs are met for dying individuals in long-term care (LTC) institutional settings. This study compared receipt of religious and spiritual help in four types of LTC settings: NHs, smaller (<16 beds) RC/AL facilities, traditional RC/AL facilities, and new-model RC/AL facilities. Data were also available for religious affiliation of the facilities, size, and provision of religious and hospice services. Controlling for such factors, the importance of religion/spirituality to the decedent was the strongest predictor of the decedent's receipt of spiritual help. In addition, new-model RC/AL facilities were significantly more likely to provide help for religious and spiritual needs of decedent residents than other RC/AL types, but did not differ significantly from NHs.